Scale up proposal for the spray drying process of hebernem-s bionematicide (Nexo Revista Científica, 2023)
The need for robust spray dryer scale-up methods is essential to control critical quality attributes in the biopharmaceutical industry. In this second part, various parameters are determined such as the heat capacity of the cream (value of 3.626 kJ/kg.ºC), the enthalpies and mass flowrates of the different streams involved, the Sauter diameter (88.78 μm), the drying total time (6.90 s) and the efficiencies. A mathematical model was also obtained by using MATLABÒ software, in order to determine the main phenomenological characteristics of the evaluated spray drying process. In general, the increase in the cream feeding temperature, the powder temperature, the cream dry mass and the rotation speed of the atomizer decrease the final humidity of the powder, while the air inlet temperature and the absolute air humidity increase it. The temperature of the powder at the exit of the cyclone and the rotation speed of the atomizer disk are the variables that most influence the scale-up of spray drying. The new mathematical model obtained in this work quantitatively describes the spray-drying process of HeberNem-SÒ bionematicide.